DESCRIPTION OF MATHEMATICAL COMPREHENSION BASED ON COGNITIVE-CATEGORY STYLE ON FOUR-SIDED SHAPE TOPIC OF 8TH GRADE STUDENTS IN MTSN 1 KOTA MAKASSAR - asmaun, asmaun (Global Science Education Journal, 2019)
The research was descriptive research by using qualitative approach, The subject consists of four students of VIII.1 MTsN 1 Kota Makassar. The results of the study towards 4-sided concepts are: the pupil, who had a field-independent-cognitive style, was able to reach 5 indicators well of 6 indicators. Generally, a field-independent student understood the concepts by considering the properties of each 4-sided shape; it caused that he/she was able to achieve 4 of 5 indicators of principle comprehension which had been determined. The field-independent student, generally, understood how to use and relate the principles of 4-sided object, yet he/she were less skillful in algebra process. However, the field-dependent one has not been succeed well in reaching a 6-defined indicator; only with wholly-seen shape did the student understand the concepts of 4-sided object. But for 4-sided-conprehension principle, the student barely achieved the 5-defined indicators. The student apprehended generally on 4-sided principle limited in the principle use of a certain 4-sided object. In this case, the student has not been skillful enough to understand the relationships between the object moreover, he/she cannot use the principle to solve problems.